Three new species of the subgenus Cryobius Chaudoir, 1838 (Coleoptera: Carabidae, Pterostichus Bonelli, 1810) from the Russian Far East - Sundukov, Yurii N. (Zootaxa, 2025)
Three new species of Pterostichus subgenus Cryobius Chaudoir, 1838, are described from the southern Russian Far East: P. (C.) storozhenkoi sp. nov. from Mount Tardoki-Yani in the northern Sikhote-Alin, P. (C.) kirilli sp. nov., and P. (C.) badzhaliensis sp. nov. from the Badzhal Ridge in the northern Amur region; all are petrophiles inhabiting rocky highlands. A catalogue of seven petrophilous species of Cryobius from the Russian Far East is provided.